2010
DOI: 10.1002/pc.20980
|View full text |Cite
|
Sign up to set email alerts
|

The effects of compatibility on the mechanical properties and fatigue resistance of butyl/EPDM rubber blends

Abstract: In this study, compatibility of butyl/ethylene‐propylene‐diene rubbers in different ratios was investigated byviscometric technique. For evaluating polymer compatibility, the parameters Δb suggested by Krigbaum&Wall, ΔB and μ that were suggested by Chee were calculated. Data obtained from viscometric study were used for preparing new compound recipe. Mechanical and rheological properties of the new compounds were measured and the changes in the properties before and after thermal aging were determined. Replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Due to the absence of double bonds in the backbone, butyl rubber is stable in diluted solutions of acids or alkalies, as well as to prolonged heat exposure. Also, butyl rubber, due to its excellent properties, has found applications as materials utilized in high-pressure conditions and to damp shocks and vibrations [5,7]. The specific working range for products based on butyl rubber is from −50 to 120 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of double bonds in the backbone, butyl rubber is stable in diluted solutions of acids or alkalies, as well as to prolonged heat exposure. Also, butyl rubber, due to its excellent properties, has found applications as materials utilized in high-pressure conditions and to damp shocks and vibrations [5,7]. The specific working range for products based on butyl rubber is from −50 to 120 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitant was washed three times with acetone to remove the unreacted MAH monomer and then exposed to vacuum at 60°C for 72 hr. In addition, a commercial compatibilizer (ethylene propylene diene monomer)‐ grafted –(maleic anhydride) (EPDM‐ g ‐MAH), which was supplied by Dupont (N416) and mostly used as the flexibilizer of nylon, was also applied in this study because many researchers have found that EPDM was compatible with CIIR at low content . (For the details of CIIR‐ g ‐MAH and EPDM‐ g ‐MAH, please refer to Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…2 IIR/EPDM blends have the properties of immiscible rubbers together such as hydrocarbon and oil resistance, ozone, optical, heat and oxygen resistance and good processability which cause many successful applications in different industries, and investigations of the effect of composition ratio on curing characteristics, morphology and mechanical properties of IIR/EPDM blends are noteworthy topics. 1215 Currently, researchers are focusing on IIR/nanoclay nanocomposites 7,8 and EPDM/nanoclay nanocomposites 911 separately. As mentioned above, IIR has a limited resistance to thermal aging.…”
Section: Introductionmentioning
confidence: 99%